The role of in-service training for language teachers in the domain of language competence - Pawlak, Mirosław (Glottodidactica, 2011)
Foreign language teachers’ language competence is one of the key factors contributingto the success of instruction as it ensures the provision of a good model of the target language,enables teachers to address the problems learners encounter, and makes teaching more creative. For this reason, improving this facet of a teacher’s expertise is indispensible in in-service teacher training, either in the form of stand-alone courses or modules incorporated into more comprehensive teacher education programs. The main aim of the present paper is to emphasize the importance of language teachers’ proficiency in the language they teach, describe its dimensions, presentthe possible goals of in-service teacher education in this area, and discuss issues involved inconducting and organizing training of this kind.